Pendampingan Tarbiyah Ruhiyah di Pondok Pesantren Lansia Izzah Zam-Zam Surakarta - Sudarmadi Putra; Anis Budiriyanto (Lembaga Sosial Rumah Indonesia, 2022)
One Islamic boarding school in Surakarta concerned with the elderly is the Izzah Zam-zam Islamic Boarding School in Surakarta. Elderly people handled by this Islamic boarding school are santri (elderly) muqim and santri (elderly) ghoiru muqim. The problems of the elderly are very complete, both from declining health factors, psychological factors, and weak religious understanding, these are internal factors, not to mention external factors also approaching, from the places and facilities of Islamic boarding schools that are not adequate. This spiritual tarbiyah mentoring for elderly students uses the PAR (Participatory action research) method, it can be identified and found problems, including contributing factors, causes, leading problems, and core problems. Problem). The results of this assistance show that there is positive progress in carrying out the way of worshiping elderly students, also positive progress in reading & memorizing the Qur'an is increasing and there are always options and solutions to the psychological problems they face.